Hybrid Technique for Removal of Arsenic from Drinking Water. Issue 2 (17th November 2022) - Sarkar, Soumi; Hazra, Soumendu; Chakraborty, Kaushik; Nayak, Ananya; Saha, Prabirkumar
Abstract: Amalgamation of a supported liquid membrane (SLM) and electrocoagulation are carried out to remove As(III) and As(V) from drinking water to achieve a high treatment efficiency. The process is based on uphill transport of arsenic ions against their concentration gradients across phases and has the advantage of simultaneous extraction and recovery followed by electrocoagulation of arsenic. The aim of the process is selective separation of arsenic from drinking water and to reduce its concentration below 10 ppb. An iron‐arsenic precipitate is obtained by using an iron anode and the said precipitate is a value‐added saleable product. Various adsorption isotherms are evaluated to understand the removal mechanism of arsenic by the formation of iron‐arsenic precipitates. The Freundlich isotherm and Dubinin‐Radushkevich model are found to fit well with the adsorption data of the removal of arsenic ions. Abstract : Amalgamation of a supported liquid membrane and electrocoagulation are performed to remove As(III) and As(V) from drinking water. For the first time, simultaneous extraction and recovery followed by electrocoagulation of arsenic for selective separation of arsenic is introduced. Using an iron anode, an iron‐arsenic precipitate is obtained which is considered as a value‐added saleable product.